PENGEMBANGAN WILAYAH MELALUI PENATAAN RUANG KAWASAN HUTAN - Epi Syahadat; Elvida Yosefi Suryandari; Andri Setiadi Kurniawan (Jurnal Analisis Kebijakan Kehutanan, 2019)
Spatial planning that only prioritizes economic interests has serious environmental impacts. The aims of this paper are: 1) Reviewing spatial planning policy based on spatial plans, 2) Identifying problems of spatial arrangement of forest area, and 3) Finding strategy for solving spatial settlement problems. The result of the study shows that there is disharmony between spatial planning policies of the Ministry of Home Affairs and the Ministry of Environment and Forestry, it requires harmonization and synchronization in its implementation. Problems in spatial planning are: 1) Spatial planning in several regions has not received the main proportion as a basic instrument for the preparation of regional development program plans, 2) Conflict of spatial use between society and government, 3) Dichotomy of interest in spatial plans from excavating local revenue from natural resources without and or less attention to environmental impacts and space, 4) Inefficiency of spatial planning institute as well as supervision of space utilization. Strategy to solve spatial problems in revised spatial plans can be implemented through: 1) Changing designation and function of forest area, 2) Integrating teamwork acceleration of forest area designation and function, and 3) Implementating forest area utilization audit based on sustainability forest.